SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN OPERATOR SELULER MENGGUNAKAN METODE MULTI-OBJECTIVE OPTIMIZATION ON THE BASIS OF RATIO ANALYSIS (MOORA) - Khairun Nisa Arifin Nur; Sundari Retno Andani; Poningsih Poningsih (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2018)
Pematangsiantar  is a developing city in North Sumatra, so it is not surprising that there are a lot of freight forwarding partners that offer goods delivery services to peoples such as POS Indonesia, JNE, JET Express, J & T Express and SiCepat Express. Many factors that influence people, especially online shop users on the selection of freight forwarding companies, such as the length of delivery, price, type of fleet, range, to company experience. Then it is necessary to build a system that helps the community in taking a decision. The model used to build this Decision Support System uses the Multi-Objective Optimization On The Base Of Ratio Analysis Method which is expected to provide convenience for people in the selection of cellular operators that they will use.Keywords: Decision Support System, MOORA, Online Shop, delivery services